2020
DOI: 10.1080/00220272.2020.1716391
|View full text |Cite
|
Sign up to set email alerts
|

Social and emotional skills in curriculum reform: a red line for measurability?

Abstract: This article applies a current example of curriculum reform to investigate mechanisms driving the push for international comparative assessment of social and emotional skills in contemporary education. Using a combination of bibliometric and content analysis the article identifies key sources in the recent Norwegian curriculum reform. The article considers how understanding and measurability of social and emotional skills is negotiated in policy documents and the cited knowledge base. Nine international source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…In addition, the need to understand the interactions between social-emotional learning, learning, and school effectiveness has also been presented (Fitzgerald, 2020;Fricke et al, 2021). Although some researchers (Restad & Mølstad, 2021) have cautioned against formalised assessment of social-emotional learning, the importance of the acknowledgment of social-emotional learning nevertheless enjoys wide recognition (Fitzgerald, 2020;Fricke et al, 2021).…”
Section: Recommendationsmentioning
confidence: 99%
“…In addition, the need to understand the interactions between social-emotional learning, learning, and school effectiveness has also been presented (Fitzgerald, 2020;Fricke et al, 2021). Although some researchers (Restad & Mølstad, 2021) have cautioned against formalised assessment of social-emotional learning, the importance of the acknowledgment of social-emotional learning nevertheless enjoys wide recognition (Fitzgerald, 2020;Fricke et al, 2021).…”
Section: Recommendationsmentioning
confidence: 99%
“…) tillempes til en norsk skolekontekst, har blitt undersøkt med utgangspunkt i konsepter som kompetanse/danning (Mausethagen, 2013) og selvregulering (Riese et al, 2020), men også med en bredere orientering, for eksempel mot elevsyn (Hilt et al, 2019) og laererroller (Mølstad & Prøitz, 2019). Disse prosessene er også et sentralt interessefelt i tekstanalytisk anlagte studier med en mer allmenn innretning, for eksempel mot innflytelsen som New Public Management utøver i norsk utdanningspolitikk (Helgøy & Homme, 2016), mot implementeringen av OECDs målsetting om å vektlegge emosjonelle og sosiale ferdigheter (Restad & Mølstad, 2020), eller mot kunnskapsbasen som har blitt valgt som utgangspunkt for de siste tiårenes skolereformer (Baek et al, 2018). Holdningene som inntas overfor innflytelsen utenfra, er ofte kritiske og ikke sjelden avvisende, for eksempel i diskusjonen av uttrykk som kompetanse (Willbergh, 2015) og dybdelaering (Melby-Lervåg, 2019).…”
Section: Innledningunclassified
“…The government thus concluded that this dilemma could be solved only by excluding these aspects of learning and development from the definition of 'competence'. Restad and Mølstad (2020) describe this decision as 'drawing a red line for measurability' and point to the result that '[t]he Norwegian curriculum does not align with the broad position of an international knowledge base that sees social and emotional skills as an equally important and integrated part of academic learning in schools' (p. 10). Leaving aside the conceptual debate on the limitations of competence as an educational concept (Willbergh, 2015), the failed attempt at introducing a broad definition of competence into the Norwegian curriculum shows how important traits of the Didaktik tradition-the autonomy of the student and the idea that Bildung is to some extent irreducible and impossible to break down and measure-are retained, at the same time as an output-based curriculum that challenges important principles in the same tradition, such as the distinction between matter and meaning and the autonomy of teachers and students, has been introduced.…”
Section: The Norwegian Contextmentioning
confidence: 99%